Advances in Conducting, Biodegradable and Biocompatible Copolymers for Biomedical Applications - da Silva, Aruã C.; Córdoba de Torresi, Susana I. (Frontiers in Materials, 2019)
Electroactive biomaterials are a new generation of “smart” biomaterials based on intrinsically conducting polymers (ICP). Among them, poly(3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPy) and polyaniline (PANI) are well known conducting polymers that present excellent electrical and optical properties emerging as main candidates for potential biomedical applications. Additionally, the biodegradability of biomaterials is very useful and desirable. In this context, biodegradable polymers based on polyesters, such as poly(D,L-lactic acid) (PDLLA), polycaprolactone (PCL) and poly(glycolic acid) (PGA) appear to be promising candidates because of their good biocompatibility and, as a consequence, they have been attracting attention as sustainable alternatives for applications in medicine. Weak molecular interaction with cells, biocompatibility, biodegradability, mechanics and topography are some of the main challenges for the use of conducting polymers as biomaterials. In order to improve their own biocompatibility, the main strategies are whether by doping with specific counter ions (biodopants) or chemically modifying the monomers with different molecules. Although conventional ICPs still present low or none biodegradability, there are relatively few examples of biodegradable electroactive polymers in the literature. Recently, novel approaches have been applied to solve the problem of lack of biodegradability of conducting polymers, mainly through (1) synthesis of a modified electroactive oligomers connected via degradable ester linkages creating block copolymers and (2) synthesis of modified electroactive and biodegradable macromonomers based on polyesters used in a second step copolymerization with conductive monomers. This mini-review focuses on developing trends, challenges and summarizes the recent advances on synthesis of conducting, biodegradable and biocompatible copolymers in terms of optimizing the chemical properties to improved response towards different cells, aiming biomedical applications.